Analysis of Key Technologies and Applications of Meteorological Service for Offshore Wind Power - Boni WANG; Feng WANG; Hangcheng GE; Fang HUANG; Xiaozhuo SANG; Min ZHANG (南方能源建设)
[Objective] Offshore wind power safety is of paramount importance. Meteorological services effectively address forecasting and warning challenges related to high waves, storm surges, severe convection and sea fog that impact wind farm safety, ensuring the secure and efficient operation of offshore wind energy projects. [Method] This paper took the meteorological services for offshore wind farms in Jiangsu as an example. By utilizing the data assimilation techniques and state-of-the-art artificial intelligence methods, combined with numerical models, it developed key technologies such as wind-wave-current forecasting for offshore wind farms, intelligent forecasting of significant wave height and storm surges, as well as high-impact weather monitoring and forecasting alerts. Ultimately, this led to the refinement of meteorological services and applications for offshore wind farms. The reflections on the empowerment of meteorology in the offshore wind power industry and the enhancement of technological integration across different sectors were presented. [Result] The results indicate that the spatial and temporal resolution of forecasting elements such as 10 m wind, 100 m wind, and wave height in offshore wind farms has been improved to 1 hour and 3 kilometers. The lead time for forecasting significant wave height and storm surge water level has increased to 72 hours, with an 85% accuracy rate for 6-hour forecasts. The lead time for severe convective warnings has been advanced by 1 hour, and sea fog warnings by half an hour, with a forecast accuracy rate of 92%. The technology has enabled refined meteorological services and applications for multiple working scenarios. [Conclusion] The application of key technologies in offshore wind farm meteorological services has effectively enhanced the safety production and O & M capabilities of offshore wind power, optimized the power generation efficiency of offshore wind turbine units, reduced the costs and losses of offshore operations, ensured the safety of offshore operations, and minimized losses of life and property. As offshore wind farms continue to evolve, meteorology will increasingly integrate with various disciplines, empowering the development of the entire offshore wind power industry chain.